PENGARUH LATIHAN SHUTTLE RUN DAN SHADOW TERHADAP KELINCAHAN FOOTWORK DALAM CABANG OLAHRAGA BULUTANGKIS - Rahmawati, Sindi; Adityatama, Firman (STKIP Melawi, 2025)
Abstract: This study aims to: (1) Determine the effect of shuttle run and shadow training on footwork agility (2) How much influence shuttle run and shadow training has on footwork agility. (3) Which training method is more effective on footwork agility. This study uses quantitative quasi-experimental design research with a two-group pre-test-post-test control group design. The data collection technique uses a footwork agility test. The statistical analysis technique uses SPSS, the analysis requirements test is carried out, namely the normality test and the homogeneity test. The conclusions of this study: (1) There is an effect of shuttle run and shadow training on footwork agility, with a t table value of -2.993 and sig. (2-tailed) 0.006 < 0.05. (2) There is a fairly effective effect of shuttle run and shadow training on footwork agility, the average value of the shuttle run group is 19.07 and the average value of the shadow group is 21.53. (3) There is a significant influence of shadow training on footwork agility, with an average NGain value of 4.87 and a standard deviation value of 1.407.Keywords: shuttle run training, shadow training, footwork agilityAbstrak: Penelitian ini bertujuan: (1) Mengetahui pengaruh latihan shuttle run dan shadow terhadap kelincahan footwork (2) Seberapa besar pengaruh latihan shuttle run dan shadow terhadap kelincahan footwork. (3) Metode latihan manakah yang lebih efektif terhadap kelincahan footwork. Penelitian ini menggunakan penelitian kuantitatif quasi-experimental design dengan two-group pretest-post test control group design. Teknik pengumpulan data menggunakan tes kelincahan footwork. Teknik analisis statistik menggunakan spss, dilakukan uji persyaratan analisis yaitu dengan uji normalitas dan uji homogenitas. Kesimpulan dari penelitian ini: (1) Adanya pengaruh latihan shuttle run dan shadow terhadap kelincahan footwork, dengan nilai t tabel -2,993 dan sig.(2-tailed) 0,006 < 0,05. (2) Adanya pengaruh yang cukup efektif dari latihan shuttle run dan shadow terhadap kelincahan footwork, nilai rata – rata kelompok shuttle run 19,07 dan nilai rata – rata kelompok shadow 21,53. (3) Adanya pengaruh yang signifikan dari latihan shadow terhadap kelincahan footwork, dengan nilai rata – rata NGain 4,87 dan nilai standard deviation 1,407.KataKunci: latihan shuttle run, latihan shadow, kelincahan footwork